Can bird abundance declines be detected by citizen science programmes? A case study using Common Cuckoo Cuculus canorus. (1st November 2017) - Sparks, T.H.; Atkinson, S.; Lewthwaite, K.; Dhap, R.; Moran, N.J.; Tryjanowski, P.
Using data from two independent UK citizen science schemes we investigate evidence for declines in abundance of Common Cuckoo Cuculus canorus, a species that is particularly easy to record. One of the schemes (Nature's Calendar) involves phenological recording across various taxa and is open to the general public, the other (BirdTrack) targets more committed birdwatchers. Results show a very strong correlation between the two schemes and confirm their ability to detect the marked decline in the abundance of Common Cuckoo in the UK in the 21st century. Furthermore, the first scheme allows some tentative regional comparisons with data from a century earlier, and suggests regional differences in Common Cuckoo decline over the longer term.